A 2.4 GHz receiver in silicon-on-sapphire - Peters, Michael (Kansas State University, 2013)
From 2004 to 2008, Kansas State University's Electrical and Computer Engineering (ECE) department, along with the NASA Jet Propulsion Laboratory and Peregrine Semiconductor, researched design techniques for producing a low-power, 400 MHz micro-transceiver suitable for future use on Mars scout missions. In 2012, Dr. Kuhn's Digital Radio Hardware Design class, ECE765, adapted the K-State circuit designs from this research project to investigate the possibility of producing a 2.4 GHz micro-transceiver in Peregrine Semiconductor’s newer 0.25 [mu]m Silicon on Sapphire process. This report expands upon the work completed in the Digital Radio Hardware Design (ECE765) course. The schematics and layout of the subsections of the receiver portion of the micro-transceiver chip, consisting of a transmit/receive switch, low-noise amplifier, mixer, intermediate-frequency amplifiers, and an analog-to-digital converter are described. Circuits designed to date require a total of 15 mW to operate. This report is intended as a guide for future students who will take over this project, make modifications, adapt the transmit portion of the micro-transceiver from previous work, and finish layout before fabrication of a full 2.4 GHz prototype chip.
Keywords: 2.4 GHz receiver; Electrical Engineering (0544)